2012
DOI: 10.1371/journal.pone.0042725
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila EYA Regulates the Immune Response against DNA through an Evolutionarily Conserved Threonine Phosphatase Motif

Abstract: Innate immune responses against DNA are essential to counter both pathogen infections and tissue damages. Mammalian EYAs were recently shown to play a role in regulating the innate immune responses against DNA. Here, we demonstrate that the unique Drosophila eya gene is also involved in the response specific to DNA. Haploinsufficiency of eya in mutants deficient for lysosomal DNase activity (DNaseII) reduces antimicrobial peptide gene expression, a hallmark for immune responses in flies. Like the mammalian ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 55 publications
2
41
1
Order By: Relevance
“…Another possibility is that Eya might modulate the composition or function of such complexes via its phosphothreonine phosphatase activity. Eya's threonine phosphatase activity has been implicated in innate immunity in both mammals and Drosophila, and although substrates have not been identified, cytoplasmic activity was implied by the identified interactions (Okabe et al 2009;Liu et al 2012). Intriguingly, the Jak/Stat pathway is relevant to innate immunity in both Drosophila and mammals (reviewed in Perrimon 2004 andO'Shea andPlenge 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that Eya might modulate the composition or function of such complexes via its phosphothreonine phosphatase activity. Eya's threonine phosphatase activity has been implicated in innate immunity in both mammals and Drosophila, and although substrates have not been identified, cytoplasmic activity was implied by the identified interactions (Okabe et al 2009;Liu et al 2012). Intriguingly, the Jak/Stat pathway is relevant to innate immunity in both Drosophila and mammals (reviewed in Perrimon 2004 andO'Shea andPlenge 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although Eya's tyrosine phosphatase is not required for normal development in Drosophila (Jin et al 2013), in mammals it dephosphorylates H2AX to promote repair and survival in response to DNA damage (Cook et al 2009;Krishnan et al 2009) and aPKCz to direct lung epithelial polarity and morphogenesis (El-Hashash et al 2012). Eya's threonine phosphatase is less well characterized, but appears to act both cytoplasmically to regulate innate immunity and nuclearly to provide transactivation and regulate the activity of other transcription factors (Okabe et al 2009;Liu et al 2012;Xu et al 2014;Jin and Mardon 2016).…”
mentioning
confidence: 99%
“…gut) (12). Further, it is not only activated by Gram-negative bacteria, but can react in the absence of infection to endogenous ligands, namely DNA (13,14).…”
mentioning
confidence: 99%
“…Whereas earlier studies had relied on overexpression-and misexpression-based genetic assays to show compromised output from phosphatase-dead Eya (39,40,49,56,57), Percentages of amino acid identities and similarities were calculated using LALIGN and are shown above and below the diagonal white line, respectively. Percentile bins are colored from dark to light in descending order.…”
Section: The Great Debate: Is Eya's Tyrosine Phosphatase Activity Dedmentioning
confidence: 99%
“…3). Although the catalytic mechanism and protein fold remain unknown, two follow-up studies identified mouse Eya3 as having the strongest in vitro threonine phosphatase activity of the four Eya paralogs, defined more precisely the sequence boundaries of the domain (93), and showed that both Eya's threonine phosphatase activity and its role in regulating innate immunity are likely to be conserved in Drosophila (57). The latter conclusion was based on heat shockdriven rescue transgenes, and so given the hard lesson with the tyrosine phosphatase activity (55), it will need to be confirmed with genomic constructs.…”
Section: Déjà Vu All Over Again-eya Is a Noncanonical Threonine Phospmentioning
confidence: 99%